2017
DOI: 10.1002/bjs.10396
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of operative experiences of general surgery trainees during training

Abstract: Background: General surgical training curricula around the world set defined operative numbers to be achieved before completion of training. However, there are few studies reporting total operative experience in training. This systematic review aimed to quantify the published global operative experience at completion of training in general surgery.Methods: Electronic databases were searched systematically for articles in any language relating to operative experience in trainees completing postgraduate general … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 40 publications
0
33
0
5
Order By: Relevance
“…What is apparent in contemporary training was demonstrated by a meta-analysis of 12 studies that reported the actual numbers of inguinal hernia repairs performed by general surgery trainees [15]. Two of these studies were from the UK, one from Thailand and nine from the USA [58][59][60][61][62][63][64][65][66][67][68][69].…”
Section: General Surgery Training and Hernia Repairmentioning
confidence: 99%
See 2 more Smart Citations
“…What is apparent in contemporary training was demonstrated by a meta-analysis of 12 studies that reported the actual numbers of inguinal hernia repairs performed by general surgery trainees [15]. Two of these studies were from the UK, one from Thailand and nine from the USA [58][59][60][61][62][63][64][65][66][67][68][69].…”
Section: General Surgery Training and Hernia Repairmentioning
confidence: 99%
“…"General surgery training has the intention of training surgeons to a standard for independent practice" [15]. "But there is no worldwide standardization of expected operative experience in general surgery training and various surgical curricula requirements invariably will differ" [15]. "For example, the UK demands 1600 procedures by completion of training and the USA requires 750" [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During each rotation, trainees must perform or assist in a minimum of 100 ‘major’ surgical cases per rotation (i.e. a minimum of 800 ‘major’ procedures in total) . Humanitarian and disaster surgery is referenced in the general surgery syllabus, with trainees required to demonstrate a ‘clear understanding of a potential disaster, humanitarian and military responsibilities of a general surgeon’ .…”
Section: Contemporary General Surgical Trainingmentioning
confidence: 99%
“…a minimum of 800 'major' procedures in total). 30 Humanitarian and disaster surgery is referenced in the general surgery syllabus, with trainees required to demonstrate a 'clear understanding of a potential disaster, humanitarian and military responsibilities of a general surgeon'. 29 After fellowship, many general surgeons undertake further training in subspecialties including hepato-pancreatico-biliary, upper gastrointestinal, breast and endocrine, colorectal and trauma.…”
Section: Contemporary General Surgical Trainingmentioning
confidence: 99%